Inflation and Asset Returns in a Monetary Economy. - Marshall, David A (Journal of Finance, 1992)
Postwar U.S. data are characterized by negative correlations between real equity returns and inflation and by positive correlations between real equity returns and money growth. These patterns are closely matched quantitatively by an equilibrium monetary asset pricing model. The model also implies negative correlations between expected.asset returns and expected inflation, and it predicts that the inflation-asset return correlation will be more strongly negative when inflation is generated by fluctuations in real economic activity than when it is generated by monetary fluctuations.